Sports Data Mining - Schumaker, Robert P.; Solieman, Osama K.; Chen, Hsinchun; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2010)
Data mining is the process of extracting hidden patterns from data, and it$1 (Bs commonly used in business, bioinformatics, counter-terrorism, and, increasingly, in professional sports. First popularized in Michael Lewis$1 (Bbest-selling Moneyball: The Art of Winning An Unfair Game, it has become an intrinsic part of all professional sports the world over, from baseball to cricket to soccer. While an industry has developed based on statistical analysis services for any given sport, or even for betting behavior analysis on these sports, no research-level book has considered the subject in any detail until now. Sports Data Mining brings together in one place the state of the art as it concerns an international array of sports: baseball, football, basketball, soccer, and greyhound racing are all covered, and the authors (including Hsinchun Chen, one of the most respected experts in data mining in the world) present the latest research, developments, software available, and applications for each sport. They even examine the hidden patterns in gaming and wagering, along with the most common systems for wager analysis. Integrated Series in Information Systems (IS2) strives to publish scholarly work in the technical as well as the organizational side of the field. This series contains three sub-series including: expository and research monographs, integrative handbooks, and edited volumes, focusing on the state-of-the-art of application domains and/or reference disciplines, as related to information systems. In a parallel effort - recognizing that some of the cutting edge research in IS comes from doctoral research - selected dissertations are also published in the monograph section of the series.s
Sports Data Mining: The Field -- Sports Data Mining Methodology -- Data Sources for Sports -- Research in Sports Statistics -- Tools and Systems for Sports Data Analysis -- Predictive Modeling for Sports and Gaming -- Multimedia and Video Analysis for Sports -- Web Sports Data Extraction and Visualization -- Open Source Data Mining Tools for Sports -- Greyhound Racing Using Neural Networks: A Case Study -- Greyhound Racing Using Support Vector Machines: A Case Study -- Betting and Gaming -- Conclusions.
Keywords: Computer science; Data mining; Economics -- Statistics; Operations research; Management information systems; Computer Science; Data Mining and Knowledge Discovery; Business Information Systems; Operation Research/Decision Theory; Statistics for Business/Economics/Mathematical Finance/Insurance.